Menganalisis Karakter Anak Berkebutuhan Khusus Penyandang Tunawicara Di Sekolah Dasar - Maliyan Karenina; Leni Marlina; Dion Apri Adi Saputra; Opi Andriani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Education is an effort to improve the quality of human resources. Education can be obtained through formal or non-formal institutions.Informal education institutions there are regular classes and inclusive classes.Where in the class there are not only regularchildren but also some children with special needs. Children with special needs (ABK) are defined as individuals who have different characters from other individuals .Inparticular,children with special needs show physical, ability, and emotional characteristics that are lower or higherthan regular children of their age imposed in society.Likechildren with special needs who are speech impaired. Children with special needs with disabilities are people who experience abnormalities both in terms of pronunciation (articulation). Thus, education is not only for regularchildren,but children with special needs arealsoentitledtoaproperschool.Itisalso